The subfamily Mendesellinae (Hymenoptera: Braconidae) in Brazil, with the description of six new species - Bortoni, Marco Aurélio; Souza-Gessner, Carolina Da Silva; Penteado-Dias, Angélica Maria (Zootaxa, 2016)
In this paper, we study the Mendesellinae wasps from Brazil deposited at Departamento de Ecologia e Biologia Evolutiva da Universidade Federal de São Carlos, São Carlos, SP, Brazil collection. Two new species of Epsilogaster (E. masoni sp. n. and E. whitfieldi sp. n.) and four new species of Mendesella (M. albipleura sp. n., M. itatiaia sp. n., M. japi sp. n., M. yamadai sp. n.) are described and illustrated.